Successful treatment of cutaneous leishmaniasis unresponsive to conventional drugs with itraconazole - Kamran, Tauseef (Journal of Pakistan Association of Dermatologists, 2022)
Leishmaniasis is a disease caused by a parasite of Leishmania Genus, transmitted by prick of an infected sandfly. The disease presents clinically with cutaneous, mucocutaneous or visceral form, depending upon the type of infective species and the immune status of the person. Antimonial drugs are first line of treatment for all clinical forms. Amphotericin B is second choice drug. We report a young male with cutaneous leishmaniasis unresponsive to conventional drugs successfully treated with itraconazole.